Analysis of the Religious Behavior of the Bogor Society in the Era of the Covid-19 Pandemic - Norman, Efrita; Junaedi, Dedi; Romli, Moh; Arsyad, M. Rizal; Supriyatna, Rio Kartika (International Conference on Islamic Studies, 2021)
The Covid-19 pandemic has made many multidimensional and multisectoral changes. This study aims to analyze the impact of the pandemic on the religiosity (religious behavior) of the community, especially the Laa Roiba National IAI academic community, Bogor. Descriptive-qualitative analytical method was used as a research method with a sample of the academic community of IAI National Laa Roiba Bogor. The pandemic that lasted more than 18 months had a real impact on the religious behavior of the people of Bogor Regency. Before the pandemic, most people used to pray in congregation at the nearest mosque/musholla. During the pandemic, most people choose to pray at home or alone. Entering the transition period, some began to congregate to the mosque/musholla, and when PPKM was implemented, some of them returned to their homes. Meanwhile, for Friday prayers and Eid prayers, some residents were still looking for mosques/musholla to perform them. Iftar together, family gathering (silaturahim), and religious study tend to decrease, except online via Zoom and Google Meet or social media such as WAG and Facebook. In the midst of limitations, the infaq tradition tends to persist, even a small number of residents increase their infaq. Likewise, feelings of religiosity and levels of personal piety are acknowledged to have increased after the pandemic.